Postcard : Notice of meeting - Arne, Betty L.
1938-01-08 038-0171-002 BASQUE CHILDREN'S COMMITEE Please note that the next Meeting of the Committee will be held at 35, Marsham Street S.W.1. on Wed. January 12th, at 5.30 p.m. Betty L. Arne, Secretary. 292/946/38/171(II)